Impact of financial market development on housing prices: Evidence from China - Zhang, Wencheng; Masron, Tajul Ariffin (International Journal of Strategic Property Management, 2025)
Housing prices in cities of China had soared by 70% from 2012 to 2021, attracting increasing public concern. Financial market development may suppress housing prices by allowing speculators to channel capital into financial markets rather than merely into the property sector, whereby it plays a critical role in shaping housing prices theoretically. This study aims to investigate the impact of financial market development on housing prices with a sample of 261 cities in China from 2011 to 2021, concluding that financial market development is negatively related to housing prices based on the GMM model. Correspondingly, a potential policy to decrease housing prices is to promote financial market development.